The state of environmental education in Polish and Czech universities. (1st January 2003) - Urbaniec, Maria; Krivanek, Tomas; Brauweiler, Jana; Kramer, Matthias
An appropriate university education is necessary to improve our environment. In consideration of this, an analysis of the syllabi of the Polish and Czech universities, focusing on the topics of environmental management and the protection of nature, was conducted by the International Graduate School IHI Zittau's Faculty of Business Administration. The results of this analysis can be compared with the situation at several Czech and Polish universities which offer environmentally-oriented subjects but tend to mention problems in environmental management only marginally. An international comparison in the form of a strength/weakness analysis in these countries has been conducted.